Pembelajaran Fisika Berbantuan Bahan Ajar Berbasis Kontekstual dengan Mengintegrasi Kearifan Lokal Untuk Meningkatkan Penguasaan Konsep Fisika - Muhammad Satriawan; Muhammad Subhan; Fatimah Fatimah (Universitas PGRI Semarang, 2017)
This research is a quasi experimental research that aims to determine the differences and the improvement of mastery of physics concepts in the classroom using contextual teaching materials that integrated local wisdom with classes using conventional teaching materials. The research design used was pretest posttest control group design. Both the experimental and control classes are given equal treatment, but the experimental class uses contextual teaching materials that integrate local wisdom while the control class uses conventional teaching materials. The number of students in the experimental class is 25 students while the control class is 30 Students. The data analysis used parametric statistics with a two tailed t test to determine the difference and the N-gain test to find out the improvement of student conceptualization. The two tailed t test used SPSS 20 software assistance in the data analysis process. Based on result of data analysis that obtained Sig value. (2-tailed) by 0.000 <0.01 (α = 1%). This shows that there is a very significant difference between physics learning through problem solving method using contextual teaching materials with physics learning through problem solving using conventional teaching materials. In addition, based on the N-gain calculation the average value of N-gain for the experimental class is 0.87 with the high category whereas the average value of N-gain for the control class is 0.65. This shows that the experimental class where the physics learning using materials Contextual teaching has increased the mastery of the concept higher than the control class that uses conventional teaching materials.